Comparative efficacy and safety of dupilumab versus newly approved biologics and JAKi in pediatric atopic dermatitis: A systematic review and network meta-analysis - Qiwei Liao; Hanwen Pan; Yixin Guo; Yuxiang Lan; Zhuo Huang; Peiyi Wu (PLoS ONE, 2025)
Background The newly approved biologics and Janus kinase inhibitors (JAKi) for pediatric atopic dermatitis (AD) offer additional options for clinical treatment. However, the efficacy and safety differences compared to the first approved biologic, dupilumab, remain unclear. Therefore, a network meta-analysis was conducted to evaluate these differences and identify potentially superior agents. Methods This systematic review was PROSPERO-registered (CRD42024583658). Randomized controlled trials involving pediatric patients (<18 years old) published in PubMed, Embase, Web of Science, and the Cochrane Library up to October 27, 2024 were searched and screened. RevMan software was utilized for quality assessment, and  meta-analysis was performed using R version 4.4.1. Efficacy measures included the Investigator’s Global Assessment (IGA), the Numeric Rating Scale for Itch (NRS), and the Eczema Area and Severity Index (EASI). The results of these measures were expressed as odds ratios (OR), while treatment rankings of different interventions were determined using the P-score. Result This study included 11 trials involving 7 agents and 2,352 pediatric patients. The results indicated that dupilumab (300 mg) showed better outcomes than placebo in IGA-0/1 (OR =  4.68, 95% CI: 2.53–8.63), NRS-4 (OR =  6.75, 95% CI: 3.85–11.86), and all EASI outcomes. Tralokinumab may be the most effective option for alleviating pruritus (P-score for NRS-4, 0.8447). Upadacitinib (30 mg) performed best in IGA-0/1 (P-score, 0.9414), EASI-90 (P-score, 0.9926), and EASI-75 (P-score, 0.9707). Dupilumab (300 mg) had a higher risk of nasopharyngitis compared to placebo (OR = 2.15, 95%CI: 1.04–4.43). Compared to both placebo and dupilumab (300 mg), adverse event rates were higher with upadacitinib (15 mg and 30 mg), and upper respiratory tract infection risk was elevated with baricitinib (2 mg and 4 mg) and tralokinumab (300 mg). Conclusion The efficacy of dupilumab for pediatric AD remains substantial, while other agents including upadacitinib, delgocitinib, and tralokinumab also present certain advantages. Future clinical trials may necessitate further evaluation of safety concerns.